Synthesis and characterization of thermochromic la 0.75 Ca 0.25MnO3 perovskite manganites nano-powders by microwave-assisted solution combustion synthesis - Kahatta, Sagulthai; Techitdheera, Wicharn; Chaiyo, Nopsiri; Pecharapa, Wisanu; Vittayakorn, Naratip (My University, 2014)
The microwave-assisted solution combustion synthesis was developed for application with initially synthesized thermochromic perovskite manganese oxide La0.75Ca0.25MnO3 nano-powders. Dry and very fine powders were obtained after one-step combustion reaction for less than 10 min in a modified domestic microwave oven. The thermal behavior, phase formation and purity of the precursor, and as-synthesized and calcined powders, were investigated by TGA/DTA, X-ray diffraction (XRD) and FT-IR techniques. The morphology of the powder obtained was characterized using a scanning electron microscope (SEM). The XRD pattern and FT-IR results showed that as-synthesized La 0.75Ca0.25MnO3 powders were crystalline, and the monophasic perovskite phase occurred with an average crystallite size of 30.46 ± 5.54 nm for 6 h at a relatively low calcination temperature of 900°C. The small particle size obtained by SEM suggested a high specific surface area and high sinterability. This method was found to be simple, rapid and cheap, and an effective way to prepare nano-size perovskite powders. © 2014 Taylor and Francis Group, LLC.
Keywords: combustion synthesis; La 0.75Ca 0.25MnO3; manganites; perovskite